Convergences and dissonances within the Bismarckian welfare paradigm: a critical assessment of the impacts of Hartz-IV on the German unemployment insurance system - Treuke, Stephan (Faculdade de Filosofia e Ciências, 2018)
The paper deals with the repercussions of Hartz-IV on the German welfare system, implemented in 2005 in order to stimulate the labour market structure and to meet contemporary socio-economic and demographic challenges. Focussing on the convergences and dissonances between the historically contingent Bismarckian welfare paradigm and the Hartz-IV reform on the basis of Esping-Andersen’s typology of welfare regimes, it critically examines the modifications introduced into the system of unemployment insurance. Despite the overall reduction of the unemployment rate, the dualization between either the income-based unemployment benefit I (ALG-1), which guarantees the protection of the socio-occupational status, or the means-tested unemployment benefit II (ALG-2), providing for the strict minimum assistance to the jobless, has widened socio-economic inequalities. Evidence can be found for the introduction of recommodifying mechanisms, with regards to the tightening of eligibility criteria affecting the access to the ALG-1 and with regards to the implementation of the ALG-2 with a strong responsabilization of the recipients. Furthermore, an erosion of the principle of subsidiarity can be noticed, coupled with a formalweakening of the male breadwinner’s responsibility as the main income provider. Finally, the reforms have reaffirmed the rigidity of the social classes in Germany, thus creating structural obstacles to the economic upward mobility of the working poor. While the flexibility and greater absorbability of the employment market considerably increased German’s economic competitivity, the future yet has to prove whether the growing segment of working poor will be able to upgrade to full employment and social security coverage. Keywords: German Welfare System; Unemployment Insurance; Hartz-IV; Labour Market.     Recebido em: março/2017 Aprovado: maio/2018.